HARMONISASI HUKUM TERHADAP MEANINGFUL PARTICIPATION PADA PEMBENTUKAN PERATURAN PERUNDANG-UNDANGAN BERDASARKAN UNDANG-UNDANG NOMOR 13 TAHUN - Ansor, Ansor (Universitas Harapan Medan, 2024)
Harmonisation of laws and regulations on public participation in the formation of laws and regulations is important/urgent to determine the quality of laws promulgated by the DPR together with the President. This is because community participation is not only about participating in the formation of the law but also determining whether the law will be accepted or rejected by the community after it is implemented. The formulation of the problem in this research is How is the basic concept of legal harmonisation of Meaningful Participation in the formation of laws and regulations based on Law Number 13 of 2022. The method of legal research is normative juridical or library legal research (search library), by analysing literature or secondary data relevant to the topic. This research is descriptive analytical, the data obtained and processed and analysed to provide a comprehensive picture of the basic concepts of harmonisation of the principles of meaningful public participation, with data collection methods through document studies. The results of the research show that harmonisation of laws and regulations has been implemented, but only the implementation of the content of Article 96 Paragraph (1) reads: The public has the right to provide input orally and/or in writing in the formation of laws and regulations; The public has the right to provide input orally and/or in writing in the formation of laws and regulations. The content of the article is not carried out perfectly and the legislators only stick to the formal requirements without seeing the urgency of community participation as a benchmark for the acceptance of laws in society.